Penegakan Hukum terhadap Peraturan Daerah Nomor 6 Tahun 2012 Tentang Pengelolaan Sampah dan Sanksi Hukum Serta Kendalanya Di Kota Semarang - Wulansari, Mutia; Listyarini, Dyah; Rochmani, Rochmani (Universitas Batanghari Jambi, 2024)
Waste, as a byproduct of human activities or natural processes, poses a serious issue due to its substantial and challenging quantity. Problems include waste piles in urban areas and a lack of waste disposal areas around street vendors. This research, titled